Time-resolved fluorescence imaging for quantitative histochemistry using lanthanide chelates in nanoparticles and conjugated to monoclonal antibodies. - Väisänen, V; Härmä, H; Lilja, H; Bjartell, A (2000)
Tissue and cell examinations have a potential to produce extremely valuable information about antigen quantities in samples. Using currently available methods, a truly quantitative analysis is nearly impossible. We have previously shown that immunohistochemical (IHC) detection of prostate-specific antigen and human glandular kallikrein from prostatic tissue, together with time-resolved fluorescence imaging (TRFI), is a suitable method for obtaining quantitative data from biological samples and that the signal response is linear. In this paper we show that Eu-chelate containing particles in the nanometer range are suitable labels for quantitative IHC. Even single nanoparticle molecules can be detected by TRFI and the signals measured can be readily quantitated. The signal intensity correlates very well with the amount of bound label, and the use of nanoparticles could markedly improve the sensitivity of quantitative IHC methods. TRFI provides a powerful tool for providing quantitative data about antigens or transcripts in tissue sections or cultured cells. It is also of major importance in standardization and optimization of protocols for fixation and tissue preparation, including antigen retrieval methods.